Fulfilling Psychology’s Promise: A Model of Undergraduate Psychology Education - Thompson, Ava D (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2014)
Abstract Psychologists around the world have increasingly emphasized the role of culturally-relevant psychology education and training in the development of a relevant psychology for the Majority World. However, such opportunities are limited and there are no coherent models to guide appropriate curricular development. In this article, the various components of the undergraduate psychology model developed to address the needs of the Bahamian society and to foster the development of a Bahamian and Caribbean psychology are presented. The overall structure, core values and assumptions, tripartite model of national, regional and international psychology focus, psychology of human diversity course sequence and cultural specificity are emphasized. The article concludes with a brief discussion on the implications for psychology in the Majority World and global psychology.